Traumatic Brain Injury Promotes Neurogenesis and Oligodendrogenesis in Subcortical Brain Regions of Mice - Olga Astakhova; Anna Ivanova; Ilia Komoltsev; Natalia Gulyaeva; Grigori Enikolopov; Alexander Lazutkin (Cells)
Traumatic brain injury (TBI) is one of the major causes of severe neurological disorders and long-term dysfunction in the nervous system. Besides inducing neurodegeneration, TBI alters stem cell activity and neurogenesis within primary neurogenic niches. However, the fate of dividing cells in other brain regions remains unclear despite offering potential targets for therapeutic intervention. Here, we investigated cell division and differentiation in non-neurogenic brain regions during the acute and delayed phases of TBI-induced neurodegeneration. We subjected mice to lateral fluid percussion injury (LFPI) to model TBI and analyzed them 1 or 7 weeks later. To assess cellular proliferation and differentiation, we administered 5-ethinyl-2′-deoxyuridine (EdU) and determined the number and identity of dividing cells 2 h later using markers of neuronal precursors and astro-, micro-, and oligodendroglia. Our results demonstrated a significant proliferative response in several brain regions at one week post-injury that notably diminished by seven weeks, except in the optic tract. In addition to active astro- and microgliosis, we detected oligodendrogenesis in the striatum and optic tract. Furthermore, we observed trauma-induced neurogenesis in the striatum. These findings suggest that subcortical structures, particularly the striatum and optic tract, may possess a potential for self-repair through neuronal regeneration and axon remyelination.